Bisphosphonate‐Induced Deterioration of Osteomalacia in Undiagnosed Adult Fanconi Syndrome. (5th June 2020) - Cundy, Tim; Que, Lorna; Hassan, Ibrahim M; Hughes, Louise
ABSTRACT: We describe two women with a misdiagnosed fracturing bone disease who were treated erroneously with i.v. zoledronate. Over the next year, they suffered marked clinical and radiographic deterioration in skeletal disease. Both were eventually diagnosed with hypophosphatemic osteomalacia secondary to acquired Fanconi syndrome (caused by light‐chain myeloma in one case and tenofovir treatment in the other). Appropriate treatment with phosphate supplementation was instituted with clinical improvement. These cases illustrate the importance of not missing osteomalacia in adults presenting with fractures, and the potentially damaging effects of treatment with long‐acting inhibitors of bone resorption in these circumstances. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.